Income redistribution in an economic union: Does asymmetric information legitimize centralization? - Martin Kolmar (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2002)
In this paper the role of information asymmetries between regions and a centralized authority is analyzed. In a model with inter-regional externalities due to capital mobility and a source-based tax instrument, we first derive conditions for which the optimum can be implemented by an adequately designed institution even with decentralized information about preferences for redistribution. Second we demonstrate that social-policy does not have to be centralized in order to implement the optimum. Decentralization of social policies is compatible with efficiency even when source-based taxes have to be used if decentralized authorities can rely on the enforcement of bilateral contracts.
Keywords: H23; F15; D31; 330; fiscal federalism; asymmetric information; decentralization